The Genesis code : God has spoken - Lopian, Abraham; Snyder, Julie A. (S.l. : Abraham Lopian, 2011)
The Genesis Code is not just another book on the Bible spouting the same old ideology. In fact, it is the blueprint for creation. This book touches on one of the most passionate and raw nerves in human consciousness and answers some of the most fundamental questions man has sought to know throughout the ages: Why are we here? Where do we come from?